Collider Physics within the Standard Model A Primer - Altarelli, Guido; Wells, James; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is open access under a CC BY 4.0 license. With this graduate-level primer, the principles of the standard model of particle physics receive a particular skillful, personal and enduring exposition by one of the great contributors to the field. In 2013 the late Prof. Altarelli wrote: The discovery of the Higgs boson and the non-observation of new particles or exotic phenomena have made a big step towards completing the experimental confirmation of the standard model of fundamental particle interactions. It is thus a good moment for me to collect, update and improve my graduate lecture notes on quantum chromodynamics and the theory of electroweak interactions, with main focus on collider physics. I hope that these lectures can provide an introduction to the subject for the interested reader, assumed to be already familiar with quantum field theory and some basic facts in elementary particle physics as taught in undergraduate courses. (3z(BThese lecture notes are a beautiful example of Guido$1 (Bs unique pedagogical abilities and scientific vision(3y(B. From the Foreword by Gian Giudice.s
Preface -- Gauge Theories and the Standard Model -- QCD: The Theory of Strong Interactions -- The Theory of Electroweak Interactions -- References.
Keywords: Physics; Quantum field theory; String theory; Elementary particles (Physics).; Physics; Elementary Particles, Quantum Field Theory; Quantum Field Theories, String Theory